Sclerosing Mucoepidermoid Carcinoma with Eosinophilia of the Parotid Gland: A Case Report and Review of the Literature - Chen, BS, Adam; Zhang, Emma; Krabill, MD, Keith; Chen, MD, PhD*, Frank (North American Journal of Medicine and Science, 2025)
Sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE) is an extremely rare malignant tumor in the salivary gland. In this case, the patient is a 41-year-old male with no significant history who presented a slowly growing right neck mass. The ultrasound revealed a 3.7 cm complex cystic mass in the right parotid. The surgery was pursued after a non-diagnostic fine needle aspiration. Grossly, the tumor was a 3 cm tan nodule with minimal attached soft tissue. Microscopically, the tumor is relatively well demarcated with anastomosing lobules of neoplastic cells with fibrotic stroma rich in lymphoplasmacytosis and eosinophils. Focal glandular differentiation was highlighted by mucicarmine stain. Immunohistochemically, the tumor cells are diffuse positive for pancytokeratin and p40, while negative for S100, CD45, CD3 and CD20. The tumor is negative for MAML2, EWSR1, and FUS rearrangements. The diagnosis of this case is challenging because the tumor is obscured by the marked fibroinflammatory background. Our findings indicated an exceptionally rare malignant tumor in the parotid that may be clinically and pathologically misdiagnosed as other conditions. [N A J Med Sci. 2025;18(1):021-023. DOI: 10.7156/najms.2025.1801021] Key Words: sclerosing mucoepidermoid carcinoma with eosinophilia (SMECE), parotid gland carcinoma